Foraging, grooming and mate-seeking behaviors of Macropis nuda (Hymenoptera, Melittidae) and use of Lysimachia ciliata (Primulaceae) oils in larval provisions and cell linings - Cane, J. H.; Eickwort,G.C.; Wesley,F.R.; Spielholz,J. (American Midland Naturalist, 1983)
Keywords: BEHAVIOR-FORAGING; BEHAVIOR-MATING; GROOMING; LARVAE; LARVAL PROVISIONS; MELITTIDAE; NEST LINING; OLIGOLECTY; PRIMULACEAE

An evaluation of pollination mechanisms for purple prairie-clover, Dalea purpurea (Fabaceae: Amorpheae) - Cane, J. H. (American Midland Naturalist, 2006)
Purple prairie-clover (Dalea purpurea Ventenat) is a common perennial forb that flowers during mid-summer throughout the Great Plains and adjacent biomes. Seed of D. purpurea is used for prairie restoration. This study characterizes the reproductive biology of D. purpurea. Manual pollination field trials showed that D. purpurea has a mixed pollination system. It is primarily xenogamous (45% of flowers manually pollinated with outcross pollen yielded plump seeds) but partially self-compatible (19% of selfed flowers yielded seeds). Flowers neither visited by bees nor manually pollinated rarely yielded mature seed (0-6% of flowers). A review of extensive bee community surveys from sites with prairie wildflower communities revealed that D. purpurea attracts a rich and diverse native bee fauna. Managed agricultural pollinators (Apis mellifera, Megachile rotundata) also work its flowers for pollen and nectar, yielding >20,000 seeds per plant. These observations bode well both for pollinating D. purpurea in small commercial seed fields as well as for its value for sustaining native pollinator faunas in prairie restorations.
Keywords: FABACEAE; OUTCROSSING; POLLINATION; POLLINATION EFFICIENCY; SEED SET; SELF-COMPATIBILITY

Breeding biology of the threadstalk milkvetch, Astragalus filipes (Fabaceae), with a review of the genus - Watrous,K.W.; Cane, J. H. (American Midland Naturalist, 2011)
Astragalus L. (Fabaceae) is an enormous and diverse plant genus with a cosmopolitan distribution, but relatively few breeding biologies are known for its member species. Threadstalk (or basalt) milkvetch, Astragalus filipes Torrey ex. A. Gray, is common and widespread throughout the US Intermountain West, including the Great Basin. It is being studied and ultimately propagated for extensive rangeland restoration projects throughout the sagebrush steppe. Understanding the breeding biology of A. filipes will be necessary for reliable and consistent commercial seed production with this species. We examined reproductive output from four manual pollination treatments (autogamy, geitonogamy, xenogamy and distant xenogamy) in a common garden. As measures of fitness, we counted fruit and seed set, then germinated viable seeds, to assess reproductive output. This species is weakly self compatible; xenogamous pollen transfer results in nine times more seed per pollination. Pollen transfer between geographically distant seed accessions resulted in a decrease in seed germination, but no difference in fruit or seed set. Cross pollination by bees will be necessary for copious seed production by this species. In the wild, flowers of A. filipes are visited most commonly and ubiquitously by a diversity of Osmia bee species plus several bee species each of Eucera, Anthidium, Bombus and sometimes Hoplitis.
Keywords: ASTRAGALUS; BOMBUS; FABACEAE; FRUIT SET; Megachilidae; OSMIA; OUTCROSSING; POLLINATION; POLLINATOR; SEED PRODUCTION; SEED SET; SELF-COMPATIBILITY